The first contribution to lichens and lichenicolous fungi of Kivertsy National Nature Park «Tsumanska Pushcha» (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
The first data on the lichens and lichenicolous fungi of Kivertsy National Natural Park «Tsumanska Pushcha» are reported. Totally, 50 species of lichens and one lichenicolous fungus were found. Among them, Acrocordia gemmata, Arthonia radiata, Athallia pyracea, Biatora chrysantha, Catillaria nigroclavata, Chaenotheca phaeocephala, Cladonia cariosa, C. coniocraea, Coppinsidea croatica, Heterocephalacria physciacearum Graphis scripta, Lecaniella naegelii, Lecanora expallens, Lepra albescens, L. amara, Lepraria incana, L. finkii, Mycobilimbia epixanthoides, Phlyctis argena, Peltigera didactyla, Porina aenea, Physcia tenella, Placynthiella uliginosa, Polyozosia persimilis, P. sambuci, Pseudoschismatomma rufescens, Rinodina freyi, Scoliciosporum sarothamni are new to the Volyn region. Coppinsidea croatica is recorded for the first time for the lowland part of Ukraine. Rinodina freyi are new for Ukraine. This species is common in the forest areas of Asia, Europe and North America. It is a pioneer lichen on thin twigs of shrubs or damaged areas (scars) on the bark of trees. Rinodina freyi is characterized by a thin, almost inconspicuous gray thallus with flat areolas and negative reactions to chemical tests, sessile apothecia 0.4–0.7 μm in diameter with a grayish-brown thalline margin (50–70 μm thick), and Physcia-type ascospores 15–19 × 6.5–8.5 μm. Lichen communities are presented mainly by epiphytic species that grow on the bark of Alnus incana, Quercus robur, Salix fragilis. Low number of species were found sandy soil of river terraces. Acrocordia gemmata is a species that was included in the regional Red List of the Volyn region.
Keywords: Rinodina freyi, biodiversity, Volyn region, Ukraine.